Correction to: Gap Analysis Regarding Prognostication in Neurocritical Care: A Joint Statement from the German Neurocritical Care Society and the Neurocritical Care Society - Wartenberg, Katja E.; Hwang, David Y.; Haeusler, Karl Georg; Muehlschlegel, Susanne; Sakowitz, Oliver W.; Madžar, Dominik; Hamer, Hajo; Rabinstein, Alejandro A.; Greer, David M.; Hemphill, J. Claude; Meixensberger, Juergen; Varelas, Panayiotis N. (Neurocritical Care, 2019)
This article was updated to correct the spelling of Karl Georg Haeusler.
CRIS-Team Scopus Importer:2019-08-30